The challenges to get promoted into top managerial position in Petronas Carigali Sdn Bhd (PCSB): the women perspective / Muhammad Nazmi Md Nazirruddin and Nur Nasihah Ayuni Mohd - Md Nazirruddin, Muhammad Nazmi; Mohd, Nur Nasihah Ayuni (Faculty of Business and Management, 2013)
This study is about the commitment, performance and decision making towards challenges to get promoted into top managerial position. It studies about the challenges to get promoted into top managerial position in term of women perspective in PETRONAS Carigali Sdn Bhd (PCSB). In most organization domestically or internationally, the higher position in the company will be dominated by men. It was a common situation in any organization when men was chosen to be a leader or filled up the higher position in the organization. As a result, this might create perception or stereotypes towards women. Some of the problems also may related to decreasing motivation among women in conducting their jobs, discouraging women to enhance their potential skills that might be valuable to the organization and more. Due to several factors such as commitment, performance and decision making that might affect challenges to get promoted into top managerial position, the researcher decided to know deeper and do research on the relationship between factors (commitment, performance and decision making) towards challenges to get promoted into top managerial position. In this study of research, factors that influences challenges to get promoted into top managerial position act as independent variables, while challenges to get promoted into top managerial position act as dependent variable. Findings are interpreted using several methods of analysis. As a conclusion, there are relationship between commitment, performance and challenges to get promoted into top managerial position. The recommendations that been recommended is to improve compensation and benefits program and increase the effectiveness of management towards employees’ training program.